Influence of Different Commercial Modified Cassava Starches on the Physicochemical Properties of Thermoplastic Edible Films Obtained by Flat‐die Extrusion - Guz, Lucas Martín (2020)
Starch constitutes a promising resource for biodegradable packaging, but it presents several processing drawbacks when using conventional industrial equipment, such as flat-die extrusion. This work demonstrates that the replacement of native cassava starch (NS) with commercial hydrolyzed (HS) or carboxymethyl (CMS) starches diminishes the amount of energy required to process starch granules into thermoplastic films by extrusion. Homogeneous films with starch-glycerol interaction improvements are obtained when using HS or CMS instead of NS. HS films exhibit the lowest crystallinity and the highest susceptibility to water among the studied systems. Likewise, CMS films maximize Vh crystalline structure fraction and present higher Young's modulus and stress at break, and lower water vapor permeability values. In order to combine the positive properties and to overcome the limitations of each modified starch, blend films from HS:CMS (50:50 wt%) are also developed and investigated. Phase separation is observed in this system, and there are no improvements in the overall properties. The results of this investigation show that employing commercial CMS, even in very low carboxymethylation degree represents a successful strategy to improve mechanical and barrier properties of flat-die extruded films, while HS can be used to obtain water-soluble films for specific applications.